Tendencje, kierunki i paradygmaty w niemieckich badaniach i koncepcjach uczenia się dorosłych - Solarczyk-Szwec, Hanna (Wydawnictwo Naukowe UAM, 2014)
The article contains an overview of studies and concepts of adult education in Germany from the 1960s, when andragogy was formed as a discipline of science at universities, to the present. Of particular importance for the development of research on education in Germany, were four large-scale empirical team studies, commonly known as: Göttingen Study (1966), Oldenburg Study (1971-1973), Hanover College (1975), and Heidelberg Study (1979-1981), which were more closely characterised in the article from the methodological and theoretical perspective. In Germany in the 1980s, there was a clear turn in the methodology of andragogy research towards a paradigm of quantitative studies. The turn allowed to include and give a specific trait to concepts of life environment, everyday knowledge, patterns of interaction and biographicity. In the 1990s, in the German andragogy disappeared a tendency for the dominance of a selected research paradigm; a methodological concept of criss- rossing perspectives was developed, which implies the development of specific research methods, adequate for the subject of studies. Further in the text were presented concepts of adult learning emerging in the next decades. They were: key qualifications, exemplary, expansive, situational, self-organised, and directed learning as well as theories of emotional lifelong adult learning. The summary indicated characteristic features of research and theory of adult education in Germany.
Tendencies, Directions and Paradigms in the German Studies and Concepts of Adult Education
Keywords: adult education; research on learning; Germany